Dermatologic masks of Langerhans cell histiocytosis. Case report - Tatiana S. Belysheva; Timur T. Valiev; Nikolay N. Murashkin (ZAO "Consilium Medicum", 2022)
Langerhans cell histiocytosis (LCH) is a rare pathology in pediatric age with heterogeneous clinical presentation in skeletal system, skin, central nervous system, liver, spleen, lungs, lymph nodes and bone marrow. Therefore, a number of diagnostic mistakes increase and inadequate therapy administrates. For a diagnostic period, a try at treatment, LCH disseminates with organs and systems involvement and at the moment of morpho-immunologic diagnosis verification, a disease characterizes as multiorgan multiple site affection, which decreased survival rate. In the current issue a clinical case of LCH with mistaken prolonged (2 year) atopic dermatitis anamneses is presented. The absence of pronounced effect of topical therapy along with nontypical for atopic dermatitis became not an indication for skin biopsy. After appearance of systemic symptoms with anemia, leuko- and thrombocytopenia became an evidence for pediatric oncologist-hematologist consultation.